THE BIBLICAL PERSPECTIVE ON THE ROLES OF FATHERS IN CHILDREN’S UPBRINGING - Moses Adeleke Adeoye (Religio Education, 2022)
The study is a conceptual investigation of the biblical ideas that address and support the fatherly role in children’s upbringing both spiritual development and at-home training. The information was acquired using a biblical lexicon, commentaries, the internet, journals and other sources that discuss at-home instruction on children's spiritual development. The primary claim of responsibility for children’s upbringing belongs to the parents. The father’s involvement has huge implications on their children in terms of cognitive, social and emotional developmental abilities and a decrease in negative behavioural outcomes. The study exposed the fathers to the reputation of raising their children in the way of the Lord. It was deduced that God holds parents responsible for the teaching and upbringing of their children. The father-child relationship quality plays an active role in organizing family life and also strengthens the relationship with the children’s upbringing. It was recommended that Christian fathers should be educated about their role and responsibilities in children’s upbringing, live an exemplary life for their children and disengage from using abusive words or curses on their children.